THE RISKS WHEN TAKING THE DECISIONS AND THEIR INFLUENCE UPON DEVELOPMENT OF THE BUSINESS PLAN - A. A. Gorjashko (Научный вестник МГТУ ГА, 2016)
The risks are considered when taking the management decisions and their influence upon development of the business plan.